Prospective multicenter non-interventional real-world study to assess the patterns of use, effectiveness and safety of follitropin delta in routine clinical practice (the PROFILE study) - Blockeel, Christophe; Griesinger, Georg; Rago, Rocco; Larsson, Per; Sonderegger, Yum Lina Yip; Rivière, Stéphane; Laven, Joop S. E. (Frontiers in Endocrinology, 2022)
Research question: To observe the real-world utilization patterns, effectiveness and safety profile of follitropin delta in women ≥18 years naïve to ovarian stimulation undergoing in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Design: Prospective, multinational, multicenter, observational study. All IVF/ICSI treatment protocols were conducted according to routine clinical practice, including undertaking fresh/frozen transfers. Outcomes included use of dosing algorithm, follitropin delta dosing patterns, ovarian response, pregnancy rates and adverse drug reactions (ADRs). Results: The first ovarian stimulation cycle using follitropin delta was initiated in 944 women. Mean baseline demographics were: age, 33.5±4.7 years; bodyweight, 67.1±13.6 kg; anti-Müllerian hormone, 20.3±16.1 pmol/L (2.84±2.25 ng/mL). The dosing algorithm was used to calculate the follitropin delta daily starting dose in 893/944 women (94.5%). The mean difference between the calculated and prescribed daily dose was small (0.2±1.40 µg). The mean daily starting follitropin delta dose was 10.4±2.72 µg and the mean total dose administered was 104 µg. Follitropin delta dose adjustments were reported for 57/944 (6.0%) women. The mean number of retrieved oocytes was 10.1±7.03. Ongoing pregnancy at 10–11 weeks was reported for 255 women (27.0% per initiated cycle and 43.1% per fresh transfer [n=592]). Cumulative ongoing pregnancy rate after fresh and/or frozen transfer was 36.4% (344/944). Four women discontinued follitropin delta due to ADRs. Ovarian hyperstimulation syndrome (OHSS) was the most frequently reported ADR (n=37 [3.9%]); most cases of OHSS were of mild or moderate intensity (n=30 [3.2%]). Conclusions: This large real-world study of follitropin delta utilization patterns confirms its good pregnancy rates while minimizing OHSS risk during first ovarian stimulation cycle.